INDEX ASSESSMENT OF THE CONDITION OF PERIODONTAL TISSUES IN PATIENTS WITH GASTROESOPHAGEAL REFLUX DISEASE - Hasiuk, Petro; Bezushko, Alina; Vorobets, Anna; Dzetsiukh, Tetiana (Eastern Ukrainian Medical Journal, 2024)
Introduction. Significant prevalence of periodontal diseases, tendency to progress with the subsequent loss of teeth, onset at a young age, decrease in the quality of life of patients and significant financial costs determine the relevance of this medical and social problem. The problem of gastroesophageal reflux disease (GERD) is being increasingly paid attention by researchers and doctors due to the high prevalence and variety of its clinical manifestations. One of the atypical (extraordinary) syndromes of gastroesophageal reflux disease is dental. The purpose of the research was to assess the condition of periodontal tissues in patients with gastroesophageal reflux disease. Materials and methods. For the study, 65 patients with GERD were selected who had been hospitalized to the gastroenterology department of Ternopil City Hospital No. 2. In total, the sample included 34 (52.31 %) men and 31 (47.69 %) women. To identify inflammatory changes in the gum mucosa, the papillary-marginal-alveolar index (PMA) and the complex periodontal index (CPI) according to P.O. Leus (1989) were used. Statistical processing of the data obtained during the study was carried out using the licensed Microsoft Excel 2016 and Statsoft Statistica 12 statistical analysis packages. Results. As a result of our study, we found that only 18.5 % of patients suffering from GERD had clinically healthy gums. 9.2 % of patients showed signs of mild gingivitis (PMA index values were within 20 %). According to the RMA index, 33.8 % of patients in the main group were diagnosed with moderate gingivitis (values ranged from 25–50 %). In 38.5 %, manifestations of severe gingivitis were visualized (the PMA index value was more than 51 %). We have found that in patients with GERD, the manifestations of inflammatory phenomena in periodontal tissues increase with age and their severity increases. According to the data obtained when determining the CPI index, 11.2 % of patients with erosive lesions of the esophagus were diagnosed with moderate periodontal tissue damage (CPI value was (2.9 ± 0.1)). In 44.4 % of patients with the erosive form of GERD, mild periodontal tissue damage was visualized (CPI = (1.6 ± 0.1)). All patients with periodontitis secondary to erosive GERD were elderly (45–59 years, according to WHO). Only 44.4 % of patients with the erosive form of GERD and 100.0 % of patients with non-erosive GERD had no inflammation of periodontal tissue (the average CPI value did not exceed 1.0). Conclusions. Based on the studies described above, we can come to the conclusion that inflammatory processes in the tissues of the periodontal complex and oral mucosa in patients suffering from gastroesophageal reflux disease are interconnected processes that aggravate each other.